Ukhuwah Islamiyah dan Perananan Masyarakat Islam dalam Mewujudkan Perdamaian: Studi Literatur - Eva Iryani; Friscilla Wulan Tersta (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Ukhuwah is a rope between two fraternal people or more. In this case it means mutual, mutual respect, and appreciate each other help. The most important of ukhuwah is ukhuwah Islamiyah. Ukhuwah Islamiyah means brotherhood among fellow Muslims. This fraternity based on creed or faith by someone. The Islamic community played an important role in realizing peace, because peace is essentially a key staple in Islamic teachings.